2015
DOI: 10.1523/jneurosci.3558-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

The Role of G-Protein Receptor 84 in Experimental Neuropathic Pain

Abstract: G-protein receptor 84 (GPR84) is an orphan receptor that is induced markedly in monocytes/macrophages and microglia during inflammation, but its pathophysiological function is unknown. Here, we investigate the role of GPR84 in a murine model of traumatic nerve injury. Naive GPR84 knock-out (KO) mice exhibited normal behavioral responses to acute noxious stimuli, but subsequent to partial sciatic nerve ligation (PNL), KOs did not develop mechanical or thermal hypersensitivity, in contrast to wild-type (WT) litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 53 publications
(1 reference statement)
3
63
0
Order By: Relevance
“…More recently the role of GPR84 in other pathologies has been investigated: Nicol et al report a role for GPR84 in response to neuropathic pain [36], while AudoyRémus et al [37] suggest GPR84 deficiency accelerates damage in a murine Alzheimer's disease model. Maddedu et al [38] proposed that GPR84 may have a role in the inflammatory responses of microglia.…”
Section: Discussionmentioning
confidence: 99%
“…More recently the role of GPR84 in other pathologies has been investigated: Nicol et al report a role for GPR84 in response to neuropathic pain [36], while AudoyRémus et al [37] suggest GPR84 deficiency accelerates damage in a murine Alzheimer's disease model. Maddedu et al [38] proposed that GPR84 may have a role in the inflammatory responses of microglia.…”
Section: Discussionmentioning
confidence: 99%
“…G-protein-coupled receptor 84 (GPR84) is an orphan receptor that is mainly produced by macrophages during inflammation and upregulated upon sciatic nerve injury [82]. Lack of GPR84 polarizes macrophages toward M2 phenotype and inhibits the development of mechanical or thermal hypersensitivity after sciatic nerve ligation injury [82], suggesting that GPR84 is a negative regulator of macrophage M2 polarization in injured nerves. Taken together, these findings indicate that peripheral nerve injury triggers a microenvironment favoring macrophage M2 polarization via a variety of mechanisms.…”
Section: Role Of Macrophages In Peripheral Nerve Regenerationmentioning
confidence: 99%
“…However, the therapeutic application of IL-10 has been limited, CCL2-CCR2 Sciatic nerve ligation injury upregulates the expression of CCL2-CCR2 signal, which in turn polarizes macrophage to M2 phenotype [52,103,112,117,120] GPR84 Ablation of GPR84 induces macrophage M2 polarization after sciatic nerve ligation injury [82] due to the fact that the in vivo bioactive half-life of IL-10 or its peptide fragments only remains for minutes to hours [98]. Interestingly, Potas et al recently found that implantation of IL-10 conjugated electrospun poly(ε-caprolactone) (PCL) nanofibrous scaffolds in sciatic nerve effectively promotes macrophage M2 polarization up to 14 days [90].…”
Section: Role Of Macrophages In Peripheral Nerve Regenerationmentioning
confidence: 99%
“…387 Galapogos progressed this chemical into a Phase 2 proof-of-concept study in ulcerative colitis in January 2015; however, the company recently reported (but has not yet published) no clinical improvement in these studies. As Nicol et al have shown that GPR84 knockout mice do not develop mechanical or thermal hypersensitivity subsequent to partial sciatic nerve ligation, 379 it may be interesting to examine the effect of GPR84 antagonists in models of nerve cell injury. 5.1.2.…”
Section: Gpr84mentioning
confidence: 99%